2003
DOI: 10.1053/jlts.2003.50109
|View full text |Cite
|
Sign up to set email alerts
|

Adult living donor liver transplantation: Perspectives from 100 liver transplant surgeons

Abstract: The involvement of healthy living donors and the degree of technical difficulty make adult living donor liver transplantation (LDLT) different from any other surgical procedure. We surveyed 100 liver transplant surgeons to assess their views on the complex issues raised by LDLT. Data were collected at meetings on LDLT and by electronic mail. The study instrument was divided into general, donor, surgeon, recipient, and donor and recipient issues. Subjects provided the projected 1-year survival threshold that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…In this survey 72% of responders considered that transplant programs have a duty to their patients to offer adult LDLT [34]. There is general agreement however that requirements need to go further with LDLT.…”
Section: Criteria For a Ldlt Programmentioning
confidence: 97%
See 1 more Smart Citation
“…In this survey 72% of responders considered that transplant programs have a duty to their patients to offer adult LDLT [34]. There is general agreement however that requirements need to go further with LDLT.…”
Section: Criteria For a Ldlt Programmentioning
confidence: 97%
“…The question as to whether LDLT should be part of every liver transplant program was partly addressed in an interesting survey of 100 liver transplant surgeons published in 2003 [34]. In this survey 72% of responders considered that transplant programs have a duty to their patients to offer adult LDLT [34].…”
Section: Criteria For a Ldlt Programmentioning
confidence: 99%
“…Another important limitation concerned the possibility that potential donors might not have fully understood the risks associated with donation as the thresholds for the risks for morbidity and mortality in this study were outside the range considered sensible by any health care provider. Although the present study was carried out following a standardized interview process and the numerical literacy of all participants was tested, participant preferences were measured only once.…”
Section: Discussionmentioning
confidence: 99%
“…However, LDLT is a technically complex procedure that absorbs substantial human and financial resources and is ethically controversial because of the risks to donors . There is still some disagreement regarding the ethics surrounding LDLT and there is uncertainty on the range of perioperative morbidity and mortality risks that living liver donors (LLDs) will consider acceptable . To investigate some of these issues, a prospective study was designed to assess potential LLDs’ inclinations towards LDLT and to measure the strength of their choices.…”
Section: Introductionmentioning
confidence: 99%
“…There are also potential psychiatric issues for the living donors related to organ donation (Beresford 2004) as living donors are typically related to the recipient (Thalheimer and Capra 2002). In a recent survey among transplant surgeons, 77% of them indicated that the risk to the donor causes the surgeons a moral dilemma (Cotler et al 2003). All of these studies suggest that, all things being equal, there is a disutility associated with using a living-donor liver rather than a cadaveric liver for transplantation.…”
Section: Introductionmentioning
confidence: 99%